Locating female 'Voices' in the Minamata Convention on Mercury in Sub-Saharan Africa: The case of Ghana. Issue 107 (May 2020) - Hilson, Gavin; Hu, Yanfei; Kumah, Cynthia
Highlights: Countries that have ratified the Minamata Convention on Mercury are required to produce a National Action Plan (NAP). Each NAP must state how the mercury being used at artisanal and small-scale gold mines will be phased out. In most areas of sub-Saharan Africa, devising a comprehensive NAP promises to be an enormous undertaking. One of the more challenging tasks will be addressing the needs of dependent 'vulnerable populations', foremost women. This case study of Ghana provides valuable insights on how to bridge this gap. Abstract: Countries that have ratified the Minamata Convention on Mercury, a United Nations-backed international treaty designed to protect human health and the environment from releases of mercury and mercuric compounds, are required to produce a National Action Plan (NAP). Each must state, very clearly, how the mercury being used at artisanal and small-scale gold mines will be phased out. In most areas of sub-Saharan Africa, however, devising a comprehensive NAP promises to be an enormous and indeed, challenging, undertaking. Here, the institutional capacity and resources, expertise and at times, commitment needed to capture the level of detail the Minamata Secretariat expects to be included in each NAP are woefully lacking. One of the more challenging tasks ahead, given the shortage of hard data available on the sector's populations, production and activities, will be the design and implementation of appropriate educational, communication and support-related strategies for the 'vulnerable populations' who rely on work at artisanal and small-scale gold mines for their incomes. This is especially significant for women, who, despite accounting for at least 50 percent of the region's artisanal and small-gold mine workforce, mostly carry out the manual work at the lower tiers of the sector's labour hierarchies. Taking stock of this largely 'invisible' work, this paper reflects critically on the challenges with reducing women's exposure to mercury at artisanal and small-scale gold mines in sub-Saharan Africa. It draws on findings from ongoing research in Ghana, the location of one of the largest and most dynamic artisanal and small-scale gold mining sectors in the region.